The Actors' Symbiosis in the Recurrence of Slums after In-situ Housing Redevelopment Initiatives. Perspectives from Namuwongo Slum, Kampala City - Mubiru, Moses Batanda; Nankya, Lydia (Journal of African Real Estate Research, 2023)
This paper analyses the influence of various actors in the reoccurrence of slums in the city of Kampala, amidst the slum upgrading initiatives. This paper attributes such reoccurrence to the mismatch between the expectations of the actors involved in upgrading and the housing location mobility attributes of low-income households. This paper adopted a case study strategy, utilising a mixture of both qualitative and quantitative techniques. A total of 60 semi-structured questionnaires were issued to Namuwongo Slum Community, and only 52 were returned. Furthermore, 28 interviews were held. Six interviews targeted Local Council 1 chairpersons, 08 with officials from Slum Dwellers International (SDI), 04 with officials from the Ministry of Lands Housing and Urban Development (MLHUD), 03 with officials from Kampala Capital City Authority (KCCA), 04 privately practising land economists, and 03 private physical planners. From the information gathered, the influence of slum upgrading actors in the low-income household mobility and reoccurrence of the Namuwongo slum was exhibited through four thematic areas. These included: tracking the residential mobility tendencies, fit-for-purposeness of the upgrading programs/initiatives, actor coordination and the mismatch in expectation and preferences between the program actors and the low-income households. This paper, therefore argues that, actor coordination and participatory involvement of low-income slum-dwelling households enables the adequate fit-for-purposeness of the in-situ upgrading initiatives. This could also go a long way in limiting slum reoccurrence as the key drivers of household mobility would be understood and well incorporated in the programs.